The development of new synthetic methods and techniques using strong Brønsted bases - Hoteling, Garrett A., author; Bandar, Jeffrey, advisor; Miyake, Garret, committee member; Menoni, Carmen, committee member; Peebles, Christie, committee member (Colorado State University. Libraries, 2024)
Brønsted bases are indispensable tools in synthetic chemistry and, as such, deprotonation serves as a ubiquitous mode of molecular activation. By pushing the boundaries of what is possible within the acid-base reaction paradigm, unique synthetic methods and techniques can be developed. The work described in this thesis focuses on gaining a fundamental understanding of strong-base chemistry in efforts towards the development of new base-promoted synthetic methods. Herein, Brønsted bases have been investigated in two ways; 1) the design and application of benchtop-stable precatalyst salts for valuable organic superbases; and 2) the implementation of base-promoted halogen-transfer to develop benzylic oxidative coupling reactions with alkyl (hetero)arenes. This dissertation consists of five chapters. Chapters One and Three provide background and motivation for the work disclosed in this dissertation. Chapters Two, Four and Five represent project areas I have developed with Chapter Two adapted from published work and Chapters Four and Five as drafts of unpublished work. Below is a list of the chapters including a summary of the content for each. Chapter One describes the importance of organic superbases and their relevance to the synthetic community and the Bandar Group as a whole. Presented here will be the various classes of superbases and their unique properties that distinguish them from other classes of bases. Additionally, applications and known limitations to use of these bases will be discussed here. Chapter Two describes work along with Dr. Stephen J. Sujansky on the development of benchtop-stable organic superbase salts and the method for their facile in situ activation. Here, air-sensitive organic superbases form salts when mixed with carboxylic acids that are indefinitely stable on the benchtop. When combined with an epoxide additive, the carboxylate will react to open the epoxide and generate an alkoxide that can neutralize the superbase conjugate acid. This strategy is effective at promoting catalytic Michael-type additions and polymerizations as well as stoichiometric substitution and Pd-catalyzed cross-coupling reactions. This strain-release mechanism not only provides an accessible precatalyst for air-sensitive superbases but provides a new opportunity for controlling base concentration in situ. Chapter Two describes the development of the Bandar Group’s base-promoted halogen transfer research program. The history and importance of this mechanistic platform will be discussed as well as previous reports in the area by our group. In this chapter, the mechanism of base-promoted halogen-transfer is described, which enables the exchange of weakly acidic C–H bonds for C–X bonds that can be subsequently substituted with a pronucleophile in situ. This section will also provide the necessary background and motivation for Chapters Four and Five. Chapter Four describes the development of a new method for the synthesis of benzylic amines from alkyl (hetero)arenes. The development, optimization, and scope investigation of this reaction are described herein. The results of this work represent the first general approach for benzylic C–H amination, functioning on a broad scope of alkyl (hetero)arenes and amine coupling partners. Chapter Five describes the use of base-promoted halogen-transfer to enable alkyl (hetero)arene desaturation. With ethyl- and longer alkyl-substituted arenes, after benzylic halogenation, elimination takes place in the presence of excess base, a process that is competitive iv with the substitution protocol described in Chapter Two. Here, this reactivity has been exploited to develop a general desaturation technique for alkyl (hetero)arenes. Under desaturation conditions, an amine pronucleophile can be added, at which point β-addition followed by subsequent desaturation affords the β -aryl enamine, which is a diversifiable functional handle. This chapter describes the development of desaturation, cascade enamine formation, and the modification of enamine products.
Keywords: amination; superbase; precatalyst; alkyl arene